Feedback and revisions in developing writing skills in second language learners: A systematic review - Annisa, Annisa; Gusnawaty, Gusnawaty (Kajian Pendidikan, Seni, Budaya, Sosial dan Lingkungan, 2024)
Developing writing skills include many aspects. This paper presents an analysis of a systematic review of several studies from 2014 – 2022 with a total 7 studies. This systematic review is to show what teaching methods that learners use to enhance writing skills and how feedback and revision is beneficial and necessary to improve writing skills. There are various feedback and revision techniques to enhance writing skills, especially for second-language learners such as utilizing platforms like WhatsApp and Zoom until utilizing metacognitive strategies – in order for students can actively monitor and evaluate their writing progress.